Debating Economic Policy for South Africa's Post-apartheid Transition: From Scholarship and Ideology to Policy in Practice : Critical Reconstructions of Political Economy, Volume 8 - Fine, Benjamin, (Social Sciences E-Books Online, Collection 2026., 2026)
The reasons for South Africa's full and rapid post-apartheid embrace of neoliberal economic policy remain controversial. Drawing on the author's own participation in policy debates, this volume establishes there were alternatives available that were either dismissed or not even considered. Explanations for policy failings have to be sought in determinants such as globalisation, financialisation, capital flight, corporate restructuring and Black Economic Empowerment. The text offers extensive surveys of relevant literature including the developmental state, industrial and social policy, privatisation, trade policy, the Harvard School, comparative experience and the deficiencies in the country's National Development Plan and New Growth Path.